Development and Implementation of the AIDA International Registry for Patients With Still's Disease - Vitale, Antonio; Della Casa, Francesca; Lopalco, Giuseppe; Pereira, Rosa Maria; Ruscitti, Piero; Giacomelli, Roberto; Ragab, Gaafar; La Torre, Francesco; Bartoloni, Elena; Del Giudice, Emanuela; Lomater, Claudia; Emmi, Giacomo; et al. (Frontiers in Medicine, 2022)
Objective Aim of this paper is to present the design, construction, and modalities of dissemination of the AutoInflammatory Disease Alliance (AIDA) International Registry for patients with systemic juvenile idiopathic arthritis (sJIA) and adult-onset Still's disease (AOSD), which are the pediatric and adult forms of the same autoinflammatory disorder. Methods This Registry is a clinical, physician-driven, population- and electronic-based instrument implemented for the retrospective and prospective collection of real-world data. The collection of data is based on the Research Electronic Data Capture (REDCap) tool and is intended to obtain evidence drawn from routine patients' management. The collection of standardized data is thought to bring knowledge about real-life clinical research and potentially communicate with other existing and future Registries dedicated to Still's disease. Moreover, it has been conceived to be flexible enough to easily change according to future scientific acquisitions. Results Starting from June 30th to February 7th, 2022, 110 Centers from 23 Countries in 4 continents have been involved. Fifty-four of these have already obtained the approval from their local Ethics Committees. Currently, the platform counts 290 users (111 Principal Investigators, 175 Site Investigators, 2 Lead Investigators, and 2 data managers). The Registry collects baseline and follow-up data using 4449 fields organized into 14 instruments, including patient's demographics, history, clinical manifestations and symptoms, trigger/risk factors, therapies and healthcare access. Conclusions This international Registry for patients with Still's disease will allow a robust clinical research through collection of standardized data, international consultation, dissemination of knowledge, and implementation of observational studies based on wide cohorts of patients followed-up for very long periods. Solid evidence drawn from “real-life” data represents the ultimate goal of this Registry, which has been implemented to significantly improve the overall management of patients with Still's disease. NCT 05200715 available at https://clinicaltrials.gov/.